2021
DOI: 10.1136/bmjopen-2020-039490
|View full text |Cite
|
Sign up to set email alerts
|

From hospitalisation to primary care: integrative model of clinical pharmacy with patients implanted with a PICC line—research protocol for a prospective before–after study

Abstract: IntroductionClinical pharmacy improves patient safety and secures drug management using information, education and good clinical practices. However, medical device management is still unexplored, and proof of effectiveness is needed. A PICC line (peripherally inserted central catheter) is a medical device for infusion. It accesses the central venous system after being implanted in a peripheral vein. However, complications after implantation often interfere with smooth execution of the treatment. We hypothesise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…With the wide application of the Internet, the health management model based on mobile phone application software has been developed rapidly. Studies have shown that the health management model based on mobile phone application software can improve the compliance of postoperative functional exercise and promote the rehabilitation of breast cancer patients [13]. In this study, with the intelligent grip ball as the carrier, integrating the advantages of grip movement and hand functional exercise, the mobile phone application software "Intelligent grip strength system" was designed to decline the functional exercise compliance of PICC patients, promote functional exercise, improve the quality of life, and reduce the incidence of catheter-related thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…With the wide application of the Internet, the health management model based on mobile phone application software has been developed rapidly. Studies have shown that the health management model based on mobile phone application software can improve the compliance of postoperative functional exercise and promote the rehabilitation of breast cancer patients [13]. In this study, with the intelligent grip ball as the carrier, integrating the advantages of grip movement and hand functional exercise, the mobile phone application software "Intelligent grip strength system" was designed to decline the functional exercise compliance of PICC patients, promote functional exercise, improve the quality of life, and reduce the incidence of catheter-related thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the pilot design of the study and its relative associated lack of power and more studies should be conducted to confirm this trend. 21 Considering the subgroup analysis including all PICCs from both control and in-tervention groups, single-lumen PICCs showed a significant reduction in overall complications and occlusions, whereas no significant differences were reported for CRBSI and DVT. The complication risk was higher with the double-lumen PICCs performing a multivariate analysis adjusted for sex, age, indication, and PICC line duration (OR, 3.83; 95% CI, 1.46-10.07, P = 0.007).…”
Section: Discussionmentioning
confidence: 88%
“…Although our study showed a significant reduction in the use of double-lumen PICCs after the CP intervention, the number of complications was lower with the pharmacist intervention although it was not significant. This could be due to the pilot design of the study and its relative associated lack of power and more studies should be conducted to confirm this trend 21 . Considering the subgroup analysis including all PICCs from both control and intervention groups, single-lumen PICCs showed a significant reduction in overall complications and occlusions, whereas no significant differences were reported for CRBSI and DVT.…”
Section: Discussionmentioning
confidence: 94%